2006
DOI: 10.1016/j.cell.2005.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-B2 Controls Cell Motility and Adhesion during Blood-Vessel-Wall Assembly

Abstract: New blood vessels are initially formed through the assembly or sprouting of endothelial cells, but the recruitment of supporting pericytes and vascular smooth muscle cells (mural cells) ensures the formation of a mature and stable vascular network. Defective mural-cell coverage is associated with the poorly organized and leaky vasculature seen in tumors or other human diseases. Here we report that mural cells require ephrin-B2, a ligand for Eph receptor tyrosine kinases, for normal association with small-diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
389
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 403 publications
(407 citation statements)
references
References 45 publications
6
389
3
Order By: Relevance
“…Defective mural-cell coverage is associated with the poorly organized and leaky vasculature seen in tumors or other human diseases. The authors further suggest that ephrin-B2 has some cell-cell-contactindependent functions [15] during these events.…”
Section: New Insights Into Functions Outside Of the Nervous Systemmentioning
confidence: 89%
See 1 more Smart Citation
“…Defective mural-cell coverage is associated with the poorly organized and leaky vasculature seen in tumors or other human diseases. The authors further suggest that ephrin-B2 has some cell-cell-contactindependent functions [15] during these events.…”
Section: New Insights Into Functions Outside Of the Nervous Systemmentioning
confidence: 89%
“…In addition, EphB2 and ephrin-B2 mediate the interactions between the vessel endothelial cells and the adjacent mesenchymal cells [13,14]. An important new study [15] reveals that ephrin-B2 is also required for normal association between the blood-vessel endothelial cells and the supporting pericytes and vascular smooth muscle cells (mural cells). Defective mural-cell coverage is associated with the poorly organized and leaky vasculature seen in tumors or other human diseases.…”
Section: New Insights Into Functions Outside Of the Nervous Systemmentioning
confidence: 99%
“…Pdgfrb‐Cre mice (Foo et al ., 2006) were kindly provided by Ralf Adams (Max Planck Institute for Biomedicine, Münster, Germany). R26‐mTmG mice (Muzumdar et al ., 2007); obtained from the Jackson Laboratory) and Tie2‐Cre mice (Koni et al ., 2001) were described previously.…”
Section: Methodsmentioning
confidence: 99%
“…The Pdgfrb‐Cre line (Foo et al ., 2006), where Cre recombinase expression is driven by a transgenic fragment of the gene for platelet‐derived growth factor receptor β ( Pdgfrb ), has been used extensively to specifically target mural cells, namely vascular smooth muscle cells, pericytes and hepatic stellate cells; examples are given in ref (Abraham et al ., 2008; Foo et al ., 2006; Greif et al ., 2012; Henderson et al ., 2013; Jeansson et al ., 2011; Kogata et al ., 2009; Siegenthaler et al ., 2013; Stenzel et al ., 2009; Ye et al ., 2009; You et al ., 2014). We (Stanczuk et al ., 2015) and others (Klotz et al ., 2015) recently showed that Pdgfrb‐Cre unexpectedly also targets a large proportion of embryonic lymphatic endothelial cells (LECs) in the developing mesentery (Stanczuk et al ., 2015) and the heart (Klotz et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial ephrinB2 can also interact with receptors on mural cells or perivascular mesenchyme to affect vascular development (Adams et al, 1999;Oike et al, 2002;Umeda et al, 2004). Finally, ephrinB2 on nonvascular cells can also affect vascular patterning (Zhang et al, 2001;Foo et al, 2006). Thus the outcome of ephrinB2-receptor signaling may depend on the cellular context and on the involvement of other signaling components, such as growth factor receptors (Pasquale, 2005;Zhang and Hughes, 2006).…”
Section: Introductionmentioning
confidence: 99%